The religious genres of collective memory – an attempt at typology - Wójcicka, Marta (Stylistyka, 2020)
The memory genre as a model of text serves to memorize (shape) and remember (pass on) images of the past, which reproduces the picture of the past. The article is an attempt at providing typology of religious memory genres. In the first part of the article, the concept of the memory genre is presented and an attempt is made at typology of religious memory genres, making use of the conceptions of Jan Assmann who distinguished communicative and cultural kinds within collective memory. According to the author, the religious genres of cultural memory include the liturgical prayer and the fixed prayer. On the other hand, instances of the religious genres of communicative memory are the universal prayer and parish announcements. Beside these two types, the author indicates also religious genres of inter-cultural memory, which constitute a connection of different types of memory: communicative and cultural or cultural and individual. Examples of this genre are the examination of conscience and a pastoral letter. Certain genres (e.g. the liturgical prayer) are stored in collective memory in full and should be tied to, primarily, remembering – one of the four phases of memory. Then they make genres of cultural memory. Others are connected with recalling (examination of conscience, a pastoral letter, parish announcement) and are genres of communicative or inter-cultural memory.